Changes in Patient Visits After the Implementation of Insurance Billing at a Sexually Transmitted Diseases Clinic in a Medicaid Expansion State. Issue 8 (August 2019) - Jin, Harry; Marshall, Brandon D.L.; Raifman, Julia; Montgomery, Madeline; Maynard, Michaela A.; Chan, Philip A.
Abstract : Background: Medicaid expansion has led to unique opportunities for sexually transmitted disease (STD) clinics to improve the sustainability of services by billing insurance. We evaluated changes in patient visits after the implementation of insurance billing at a STD clinic in a Medicaid expansion state. Methods: The Rhode Island STD Clinic offered HIV/STD screening services at no cost to patients until October 2016, when insurance billing was implemented. Care for uninsured patients was still provided for free. We compared the clinic visits in the preinsurance period with the postinsurance period using t -tests, Poisson regressions, and a logistic regression. Results: A total of 5560 patients were seen during the preinsurance (n = 2555) and postinsurance (n = 3005) periods. Compared with the preinsurance period, the postinsurance period had a significantly higher average number of patient visits/month (212.9 vs. 250.4, P = 0.0016), including among patients who were black (36.8 vs. 50.3, P = 0.0029), Hispanic/Latino (50.8 vs. 65.8, P = 0.0018), and insured (106.3 vs. 130.1, P = 0.0025). The growth rate of uninsured (+0.10 vs. +4.11, P = 0.0026) and new patients (−4.28 vs. +1.07, P = 0.0007) also increased between the two periods. New patients whose first visit was before the billing change had greater odds (adjusted odds ratio, 2.68, 95% confidence interval, 2.09–3.44; P < 0.0001) of returning compared with new patients whose first visit was after the billing change. Conclusions: Implementation of insurance billing at a publicly funded STD clinic, with free services provided to uninsured individuals, was associated with a modest increase in patient visits and a decline in patients returning for second visits. Abstract : A study of patient volume at a publicly funded sexually transmitted disease (STD) clinic found that implementation of insurance billing may provide a sustainable model of STD care with minimal changes on patient volume.